Brain alterations associated with overweight evaluated by body mass index or body fat index in an elderly population: the PROOF study - Kassir, Radwan; Gimet, Pierre; Hupin, David; Boutet, Claire; Barthélémy, Jean-Claude; Roche, Frédéric; Celle, Sébastien (Frontiers in Endocrinology, 2023)
Background/Objectives: Obesity is a complex health issue in which the brain plays a role yet to be determined, especially in the elderly. Indeed, in the ageing population, the balance between fat and lean mass is different thus the co-influence between brain and obesity may differ between elderly and younger subjects. Our main goal is thus to explore the relationship between the brain and obesity using two different approaches to measure obesity: body mass index (BMI) and an index centered on fat mass, the body fat index (BFI). Subjects/Methods: Among the 1 011 subjects of the PROOF population, two hundred and seventy-three 75-years old subjects underwent a 3D magnetic resonance imaging as well as a dual energy X-ray absorptiometry for assessing fat mass. Voxel-based morphometry was used to explore the local differences of brain volume with obesity. Results: Higher BMI and BFI were associated with higher grey matter (GM) volume in the left cerebellum. Higher BMI and BFI were mainly associated with higher white matter volume in the left and right cerebellum and near the right medial orbital gyrus. Higher BMI was also associated with higher GM volume in the brainstem whereas higher BFI was associated with higher GM in the left middle temporal gyrus. No white matter decrease was associated with BMI or BFI. Conclusions: In the elderly, the relationship between brain and obesity does not depend on the marker of obesity. Supra-tentorial brain structures seem to be slightly associated with obesity whereas cerebellum seems to be one of the key structures related to obesity.